Perancangan Pakaian Anak Perempuan Dengan Menggunakan Aplikasi Origami Untuk Melatih Kinerja Motorik Tangan Pada Brand "Bluzh!" - Brenda Tedjadharma; Olivia Gondoputranto (Jurnal Vicidi, 2017)
In the designing process, the designer creates a child wear clothing line that adds positive value in the implication of origami that helps to train the motoric section of hand gestures in children, with young mom that had daughter in the city as the targeted market. The designing process made from qualitative research that based on middle-up segmented. The result of the research was the young moms likes a clothes that have a positive added value with bright colours, comfortable materials, and also a simple silhouette. So, the designing process, the designer used an application that can be moveable with using sew magnet. The designer used origami from fabric that inspired from japanese culture that assemble the butterflies, flowers, and also a propeller. With creating and designing brand “Bluzh!”, the designer hope that a children that wears the clothes can practice the motoric section fo hand gestures and also can be creatives with the origami. Then, it can increase the creativity of a girl